KEEFEKTIFAN BUKU AJAR BERBASIS LITERASI MATEMATIKA UNTUK MATERI “PERSAMAAN KUADRAT DAN FUNGSI KUADRAT” - Erlin Ladyawati; Sri Rahayu (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2022)
The purpose objective of this research is to determine the effectiveness of literacy-based textbook development on the material of Quadratic Equations and Quadratic Functions. The effectiveness of mathematical literacy-based textbooks for Quadratic Equations and Quadratic Functions material is determined from the value of classical learning completeness criteria and student response questionnaires that are positive. The development of this textbook uses the ADDIE model which stands for Analyze, Design, Development, Implementation, and Evaluation. From the data above, it is also obtained information that students 'responses to the use of mathematics literacy-based textbooks for Quadratic Equations and Quadratic Functions material for class IX Junior High School who answered